2020
DOI: 10.1038/s41419-020-2731-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ZnT8 on epithelial-to-mesenchymal transition and tubulointerstitial fibrosis in diabetic kidney disease

Abstract: Zinc transporter 8 (ZnT8) transports zinc ions for crystallization and storage of insulin in pancreatic beta-cells and ZnT8 dysfunction is involved in pathogenesis of diabetes. The current study aimed to investigate whether ZnT8 has effects in pathophysiology of diabetic kidney disease (DKD) by using animal models for diabetes, including STZ-induced diabetic, db/db, ZnT8-KO, ZnT8-KO-STZ and ZnT8-KO-db/db mice. Results demonstrated that urine albumin to creatinine ratio and epithelial-to-mesenchymal transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
(56 reference statements)
1
12
0
Order By: Relevance
“…Additionally, the knockdown of this lncRNA inhibited the HG-induced phosphorylation of SMAD3. Several researchers have already suggested that the inhibition of SMAD3 phosphorylation may prevent HG-induced EMT [21,22]. Our results corroborated those studies, suggesting that the knockdown of LUCAT1 inhibited the EMT of HG-treated HK-2 cells.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the knockdown of this lncRNA inhibited the HG-induced phosphorylation of SMAD3. Several researchers have already suggested that the inhibition of SMAD3 phosphorylation may prevent HG-induced EMT [21,22]. Our results corroborated those studies, suggesting that the knockdown of LUCAT1 inhibited the EMT of HG-treated HK-2 cells.…”
Section: Discussionsupporting
confidence: 91%
“…The graph illustrates that changes in lipid metabolism are also proportional to the dose and number of doses given. In addition, only minor renal lesions such as mesangial matrix expansion and basement membrane thickening were observed 16,29,30 . As can be seen from Table 3, maternal obesity aggravated both diabetic milieus and renal dysfunction in the offspring, accompanied by renal fibrosis and renal oxidative stress, which may indicate a potential approach to establishing novel DKD models 31 .…”
Section: Resultsmentioning
confidence: 95%
“…Zinc transporter 8 (ZnT8) transports zinc ions for crystallization and storage of insulin in pancreatic beta‐cells. ZnT8‐KO male mice were subsequently intercrossed with female db/db mice to generate ZnT8‐KO‐db/db mice, causing a more severe type2 DM along with insulin resistance 16 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This EndMT induced by TGF‐β through MAPK and AKT is called Smad‐independent signalling pathway (Figure 1 ). 38 , 39 Note that the Smad‐dependent and Smad‐independent pathways can coordinate the regulation of EndMT. For example, ERK MAPK crosstalks with the Smad‐dependent signalling pathway through phosphorylation of Smad2/3.…”
Section: Endmt and Dkdmentioning
confidence: 99%